Modeling neuroinflammatory interactions between microglia and astrocytes in a human iPSC-based coculture platform - Iisa Tujula; Tanja Hyvärinen; Johanna Lotila; Julia Rogal; Dimitrios Voulgaris; Lassi Sukki; Kaisa Tornberg; Katri Korpela; Henna Jäntti; Tarja Malm; Anna Herland; Pasi Kallio; et al. (Cell Communication and Signaling)
Abstract Background Microglia and astrocytes are central mediators of neuroinflammation in several neurodegenerative diseases. Their intricate crosstalk and contributions to pathogenesis remain elusive, highlighting the need for innovative in vitro approaches for investigating glial interactions in neuroinflammation. This study aimed to develop advanced human-based glial coculture models to explore the inflammatory interactions of microglia and astrocytes in vitro. Methods Human induced pluripotent stem cell (iPSC)-derived microglia and astrocytes were cultured both in conventional culture dishes and in a microfluidic coculture platform. This platform features separate compartments for both cell types, enabling the creation of distinct microenvironments with spontaneous migration of microglia toward astrocytes through interconnecting microtunnels. To induce inflammatory activation, glial cultures were stimulated with lipopolysaccharide (LPS), a combination of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), or interferon-γ (IFN-γ) for 24 h. Glial activation and interactions were analyzed with immunocytochemistry, the secretion of inflammatory factors from the culture media was measured, and microglial migration was quantified. Results Microglia–astrocyte cocultures were generated in both conventional cultures and the microfluidic platform. Inflammatory stimulation with LPS and TNF-α/IL-1β elicited cell type-specific responses in microglia and astrocytes, respectively. LPS stimulation of cocultures induced lower secretion of several inflammatory mediators, suggesting dampening of microglial inflammatory responses when cocultured with astrocytes. Notably, inflammatory interaction between glial cells was demonstrated by increased level of IL-10 after TNF-α/IL-1β stimulation in cocultures compared with monocultures. The microfluidic coculture platform enabled the parallel study of microglial migration, glial activation and phagocytic function, thereby facilitating the investigation of glial responses within distinct inflammatory microenvironments. Furthermore, glial inflammatory responses and interactions were demonstrated in the controlled microenvironments of the microfluidic coculture platform. The inflammatory coculture environment was associated with elevated levels of complement component C3, emphasizing the intricate interplay between microglia and astrocytes. Conclusions Our results depict an elaborate inflammatory interaction between iPSC-derived microglia and astrocytes via reciprocal molecular signaling. Importantly, the microfluidic coculture platform established in this study provides a more functional and advanced setup for investigating inflammatory glial interactions in vitro.